Presentation, diagnosis and treatment of breast cancer amongst women attending public hospitals in Malaysia: The time intervals and associated factors to delay / Noor Mastura Mohd Mujar - Noor Mastura, Mohd Mujar (2018)
Breast cancer is the commonest form of cancer among women in Malaysia. Although there is a scarcity of data on the relation between delays and survival, it is generally accepted that optimum outcomes are dependent on early detection and adherence to treatment. This study was conducted to evaluate the time intervals and associated factors with delays and non-adherence among breast cancer patients in Malaysia. A multicentre cross-sectional study was conducted in six public hospitals in Malaysia, involving all newly diagnosed breast cancer patients from 1st January to 31st December 2012. Data were collected through medical record reviews and interview by using structured questionnaire. Presentation delay was defined as the time taken from symptoms discovery to first presentation of more than 3 months. Diagnosis delay was defined as the time taken from first presentation to diagnosis disclosure of more than 1 month and treatment delay was defined as the time taken from diagnosis disclosure to initial treatment of more than 1 month. Meanwhile, non-adherence was categorized as any breast cancer patients refusing or discontinuing treatments due to non-medical reasons. Univariable logistic regression and multiple logistic regressions were used for analysis. A total number of 340 patients participated in this study. The median times for presentation, diagnosis, and treatment were 2.4 months, 26 days and 21 days respectively. Presentation delay was seen in 35% of the patients and the factors associated with presentation delay were Kelantan site (OR 4.78; 95% CI: 1.45, 15.7) and complementary and alternative medicine (CAM) use (OR 1.67; 95% CI: 1.01, 2.76). Diagnosis delay was seen in 41.8% and the associated factors were CAM use (OR 2.68; 95% CI: 1.63, 4.41), symptoms without lump (OR 1.98; 95% CI: 1.45, 4.12), having two or more biopsies (OR 3.02; 95% CI: 2.42, 6.45) and having a surgical biopsy (OR 2.56; 95% CI: 1.30, 5.04). Treatment delay was seen in 35.3% and it was associated with localities involving Kuala Lumpur (2) (OR 3.10; 95% CI: 1.48, 6.49), Johor (OR 4.95; 95% CI: 2.13, 11.5), Kelantan (OR 6.68; 95% CI: 2.02, iv 22.06) and Sarawak sites (OR 3.88; 95% CI: 1.52, 9.88), and those diagnosed at other hospitals (OR 2.18; 95% CI: 1.14, 4.15). Meanwhile, the proportion for non-adherence to surgery was 14%. The factors associated with non-adherence to surgery were localities involving Kuala Lumpur (2) (OR 3.41; 95% CI: 1.00, 11.60), Johor (OR 8.38; 95% CI: 2.38, 29.51) and Kelantan sites (OR 6.32; 95% CI: 1.20, 33.23) and those required mastectomy (OR 5.66; 95% CI: 1.52, 21.03). The proportion for non-adherence to chemotherapy, radiotherapy and hormonal therapy were 30.1%, 33.3% and 36.3% respectively and the only independent factor associated with non-adherence to oncology therapy was the Perak site (OR 1.42; 95% CI: 1.18, 1.97). Delays in presentation, diagnosis, and non-adherence to treatment were high among breast cancer patients attending public hospitals in Malaysia. Factors influencing delays and non-adherence were multifactorial implicating a complex interaction between variations influence of socio-culture, patients and health systems in Malaysia. Mutual collaboration from multiple areas involving patients and multidisciplinary healthcare sectors are important to reduce delays and non-adherence to treatments. Therefore, a comprehensive intervention study and audits are suggested to improve breast cancer care quality in Malaysia.